Chomsky : ideas and ideals - Smith, N. V. (Neilson Voyne) (Cambridge University Press, 1999)
Chomsky has had a major influence on modern linguistics, psychology and philosophy. In this account of his work, Chomsky's key contributions to the study of language and the mind are analysed.